When Prices Beat Production: The Dynamics of Indonesia’s Plantation Commodity Exports - Muhammad Danang Adriyanto; Muhammad Anas (Majapahit Journal of Islamic Finance and Management, 2026)
Plantation commodities are a strategic sector that contributes significantly to foreign exchange earnings and the stability of Indonesia's trade balance. This study aims to analyze the influence of commodity prices, total production, and land area on the export value of seven Indonesian plantation commodities, namely CPO, cocoa, coffee, rubber, tobacco, coconut, and tea in the 2015–2023 period. This study uses secondary data from BPS and UNCTAD and uses a panel data regression approach with the Fixed Effects Model (FEM) as the selected model based on the results of the Chow Test and the Hausman Test. The estimation results show that commodity prices and plantation land area have a positive and significant effect on export value, indicating that increases in international prices and land capacity expansion are the main determinants of long-term export growth. In contrast, total production does not show a significant effect, which is explained by the dominance of the price effect over the quantity effect amid global price volatility. These findings emphasize the importance of commodity downstreaming policies and sustainable plantation land management to strengthen the export performance of the Indonesian plantation sector.